Role Of Botanicals As Antimicrobial Agents In Management Of Dental Infections – A Review - DHINAHAR.S,; LAKSHMI.T, (International Journal of Pharma and Bio Sciences, 2011)
Streptococcus mutans is the most common cariogenic bacteria associated with dental caries. It is believed to be the chief etiologic agent in human dental caries. On the other hand Enterococcus faecalis, a gram positive cocci is associated with primary endodontic infections and persistent infections, asymptomatic chronic periradicular lesions and is responsible for the failure of root canal treatment cases. In recent years the use of and search for drugs and dietary supplements derived from botanicals have been accelerated in dental practice. Ethnopharmacologists, botanists, microbiologists, and natural-products chemists are combing the Earth for botanicals and "leads" which could be developed for treatment of infectious diseases. Traditional healers have long used botanicals to prevent or cure infectious diseases. Botanicals are rich in a wide variety of secondary metabolites, such as tannins, terpenoids, alkaloids, & flavonoids, which have been found in vitro to have antimicrobial properties. Hence this review attempts to summarize the current status of botanicals like Acacia Catechu ,Allium sativum, Azadirachta indica, Syzygium Aromaticum and Tea tree oil as potential anti microbial agents used in the management of Dental infections caused by Streptococcus mutans and Enterococcus faecalis.